Descoloração e degradação de corantes têxteis por cianobactérias - Vieira, Felipe Dias Pacheco [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The objective of the present work was to investigate the potential of cyanobacteria isolated from different environments in decolorizing eleven different types of textile dyes. For inoculum preparation 50 ml of BG-11 medium were used for the cyanobacteria Leptolyngbia CENA103, Leptolyngbia CENA104 and Phormidium autumnale UTEX1580 and 50 ml of SWBG-11 medium for Phormidium sp., Leptolyngbya sp. and Synecochoccus sp. Test tubes containing 10 ml of liquid medium and 0.02% of each dye (remazol, indigo blue, indanthrene blue RCL, drimaren blue CL-R, dispersol blue C-2R, drimaren red CL-5B, dispersol red C- 4G, indanthrene red FBB, drimaren yellow CL-R, palanil yellow 3G and indanthrene yellow 5GF) were inoculated with cyanobacteria. A spectrophotometer was used to verify the maximum absorbance of each dye and the percentage of decolorization and also thin layer chromatography (TLC). The results showed that all the tested cyanobacteria were capable to remove more than 50% of some dyes. The present study confirmed the capacity of cyanobacteria in decolorize and possibly degrade structurally different textile dyes, suggesting the possibility of their application in bioremediation studies. The data are promising, and will lead to further studies of dye degradation and its toxicicity.

O presente trabalho teve como objetivo investigar o potencial das cianobactérias isoladas de diferentes ambientes em descolorir onze diferentes tipos de corantes têxteis. Para preparo de inóculos foram utilizados 50 ml de meio BG-11 para as cianobactérias Leptolyngbia CENA103, Leptolyngbia CENA104 e Phormidium autumnale UTEX1580 e meio SWBG-11 para Phormidium sp., Leptolyngbya sp. e Synecochoccus sp. Tubos de ensaio contendo 10 ml de meio líquido e 0,02% de cada corante (remazol, índigo blue, azul indantreno RCL, azul drimaren CL-R, azul dispersol C-2R, vermelho drimaren CL-5B, vermelho dispersol C-4G, vermelho indantreno FBB, amarelo drimaren CL-R, amarelo palanil 3G e amarelo indantreno 5GF) foram inoculados com as cianobactérias. Foram utilizadas leituras em espectrofotômetro para verificar a absorbância máxima de cada corante e a porcentagem de descoloração e também cromatografia em camada delgada (CCD). Os resultados mostraram que todas as cianobactérias testadas foram capazes de descolorir mais que 50% de algum corante. O presente estudo confirmou a capacidade das cianobactérias em descolorir e possivelmente degradar corantes têxteis estruturalmente diferentes, sugerindo a possibilidade de sua aplicação em estudos de biorremediação. Esses dados são promissores, e posteriormente poderá ser estudado os produtos de degradação destes corantes e sua toxicidade.
Keywords: Bacteriologia; Biorremediação; Cianobactérias; Corantes têxteis; Cyanobacteria; Decolorization